2013
DOI: 10.1093/ejcts/ezt444
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of repair of complete atrioventricular septal defect in the current era

Abstract: Repair of cAVSD carries low mortality, but a moderate reoperation rate. An optimal time for repair of the cAVSD is between 3 and 6 months of age. Repair prior to 3 months of age and the need for cleft closure were associated with a higher degree of LAVVR at discharge. Greater LAVVR at discharge is a risk factor for reoperation regardless of age at initial repair. In the current era, Down's syndrome is not a risk factor for reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 15 publications
4
38
1
3
Order By: Relevance
“…This study was approved by the Ethics Committee of our hospital and written informed consent was obtained from all participants. Inclusion and exclusion criteria: The patients were enrolled according to the following criteria: 1) they were diagnosed with disease in the left anterior descending artery, circumflex artery or right coronary artery using coronary angiography and in NYHA (New York Heart Association) class IV according to the NYHA functional classification system; 23) 2) Invasive coronary angiography showed severe luminal stenosis > 75%; 3) prolonged mechanical ventilation (which was defined as a requirement over 72 hours of mechanical ventilation 18,24) ) was required; 4) they had stable oxygen saturation, fraction of inspired oxygen ≤ 55%, and positive end expiratory pressure ≤ 8 cm H 2 O; 5) they received dopamine at a dose of < 10 μg/kg/ minute and epinephrine at a dose of < 0.4 μg/kg/minute; 6) they had mean arterial pressure > 70 mmHg and urine output > 1 mL/kg/hour; 7) good postoperative wound healing was obtained; 8) there was no history of chronic mental illness; and 9) they had normal cognitive function.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was approved by the Ethics Committee of our hospital and written informed consent was obtained from all participants. Inclusion and exclusion criteria: The patients were enrolled according to the following criteria: 1) they were diagnosed with disease in the left anterior descending artery, circumflex artery or right coronary artery using coronary angiography and in NYHA (New York Heart Association) class IV according to the NYHA functional classification system; 23) 2) Invasive coronary angiography showed severe luminal stenosis > 75%; 3) prolonged mechanical ventilation (which was defined as a requirement over 72 hours of mechanical ventilation 18,24) ) was required; 4) they had stable oxygen saturation, fraction of inspired oxygen ≤ 55%, and positive end expiratory pressure ≤ 8 cm H 2 O; 5) they received dopamine at a dose of < 10 μg/kg/ minute and epinephrine at a dose of < 0.4 μg/kg/minute; 6) they had mean arterial pressure > 70 mmHg and urine output > 1 mL/kg/hour; 7) good postoperative wound healing was obtained; 8) there was no history of chronic mental illness; and 9) they had normal cognitive function.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] Due to a system of risk factors (such as the duration of surgery, anesthesia, clinical condition, mode of ventilator therapy, and method of weaning from mechanical ventilation), many patients should receive prolonged mechanical ventilation. [15][16][17] It was reported that the prolonged mechanical ventilation could prolong the hospital and intensive care unit (ICU) stay, 18) increase the burden of patients, and raise the risk of cerebral palsy, postoperative atrial fibrillation or ventilator-associated pneumonia.19-21) Thus, it is necessary to reduce the duration of mechanical ventilation in patients requiring prolonged mechanical ventilation.A previous study has showed that early rehabilitation therapy in ICU after CABG could significantly improve the outcomes of patients with less than 72 hours of mechanical ventilation.22) However, it is still unknown whether early rehabilitation therapy could improve the clinical outcomes and reduce the duration of mechanical ventilation in patients requiring over 72 hours of mechanical ventilation after CABG. Thus, we performed this study to evaluate the influence of early rehaFrom the…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Backer and colleagues conclude that the modified single‐patch technique is a better option when compared to double‐patch technique with regard to lower operative mortality, easy application of the surgical technique and lower incidence of reintervention due to AV valve incompetence or LV outflow tract obstruction. However, a recent study reported by Xie and associates reported successful results within a patient population in whom 92% were operated with the double‐patch technique . We believe that the shorter ACC and CPB times of the modified single‐patch technique provide an important advantage in CAVSD patients presenting with prolonged pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 82%
“…However, a recent study reported by Xie and associates reported successful results within a patient population in whom 92% were operated with the double-patch technique. 12 We believe that the shorter ACC and CPB times of the modified single-patch technique provide an important advantage in CAVSD patients presenting with prolonged pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 92%